Analisis Permasalahan Koordinasi Pemerintahan (Tinjauan Konseptual Dan Teoritis) - Febrian, Ranggi Ade (UIR PRESS, 2015)
The problem of coordination is one of the issues most important rule, the more so after the first world war increasingly difficult but also the greater meaning. In governance, coordination becomes a dominant factor several unsuccessful government in carrying out the functions of development, service delivery, and empowerment functions. Ego sectoral owned government institutions, which impressed prestige to work, ask for help or just inquire with other government agencies is a problem of coordination of government. Coordination role has always been the pivot, and guard the balance and smoothness of rotation of the